Impact of bentonite content on electrical resistivity and compressive strength of cement paste for grounding system applications - Eua-apiwatch, Sitthiphat; Arjwech, Rungroj; Chairojwattana, Apisak; Kanjanakijkasem, Worasit; Kanhari, Chaiwat; Pethrung, Sirichai (Engineering and Applied Science Research, 2025)
This study investigates the influence of bentonite content on the electrical resistivity and compressive strength of cement pastes for grounding system applications. Ordinary Portland Cement (OPC) and Non-Shrink Grout (NSG) were modified by addition of bentonite contents ranging from 0 to 50% by weight. Bulk and surface resistivity testing was conducted to evaluate the electrical properties. Compression testing was performed to determine mechanical performance. The experimental results indicated that the bulk electrical resistivity was significantly reduced due to the increased bentonite content. It decreased from 55.65 to 0.86 Ωm for OPC and from 325.55 to 0.69 Ωm for NSG after curing for 28 days. Although its electrical properties were improved, compressive strength was decreased from 18.52 to 0.06 MPa for OPC and from 18.91 to 0.07 MPa for NSG. Electrical resistivity and compressive strength exhibited strong correlations following exponential and power law relationships with moisture content, respectively. Finally, it was found that a 30% bentonite content offers an acceptable trade-off between electrical and mechanical properties for grounding applications in high-resistivity soils.